(untitled) (Indian Journal of Public Health Research & Development, 2020)
One form of health promotion for school students is the school health program in every region in Indonesia. The purpose of School Health according to the Ministry of Education and Culture in 2012 is to improve the quality of education and student achievement by improving the quality of clean and healthy life and health status of students and creating a healthy environment. This research was conducted using qualitative descriptive method with the aim of developing a model of implementing school health programs. Respondents in this study were students from junior high schools managed by the government and junior high schools managed by private parties implementing school health programs. The results of this study are expected to support existing models by improving school health management through a systems approach so that students can improve their performance through improving clean and healthy living behaviors and a healthy environment